Development of the basic soil classification of Vladimir Fridland in the classification of soils of Russia 2004/2008 - M. I. Gerasimova; N. B. Khitrov; I. I. Lebedeva (Бюллетень Почвенного института им. В.В. Докучаева, 2020)
The basic three-component classification system of soils of the world was published by V.M. Fridland in 1982, and its profile-genetic component was taken as a basis for the classification of soils of Russia (1997– 2004–2008). Unlike the former systems, in that of Fridland the priority is given to soil properties, and this conceptual background is transferred into the new Russian system. The substantive-genetic principles of both systems are implemented in diagnostic horizons and genetic properties; both systems have similar hierarchy of taxa, nomenclature, keys. Changes introduced in the classification of soils of Russia derive either of proposals forwarded in the course of its application, or of information accumulated. They concern the improvement of definitions and introduction of new diagnostic elements; however, the main principles are preserved in the existing and forthcoming versions.